Oral Plan associated with psychogenic factors: Case report (Research, Society and Development, 2021)
Oral lichen planus is a chronic mucocutaneous disease responsible for destroying the basal layer of the epithelium and, when not controlled, predisposing to malignancy. Despite its uncertain etiology, stress and anxiety have often been highlighted as promoting factors for this pathology. Thus, this study aims to report a case of a male patient with oral lichen planus (OLP) associated with psychogenic factors. Male patient, leucoderma, 32 years old, sought dental care with the main complaint that he had a white spot on his tongue, which burned when eating, and lasted for one year. During the anamnesis, the patient reported not having harmful habits or using controlled medications, however, he had a history of stress and anxiety due to the recent change in the dynamics of his personal life. On intraoral physical examination, white lesions were observed in the lateral region of the tongue and in the region of the right retromolar triangle. The clinical hypotheses of leukoplakia and lichen planus were suggested and an incisional biopsy was performed, and the surgical specimen was sent for histopathological analysis. Microscopic findings showed hyperkeratosis, acanthosis, Civatte bodies and a chronic inflammatory infiltrate containing lymphocytes, macrophages and plasma cells, leading to the final diagnosis of OLP. In addition, the patient was instructed to seek professional psychological support. The patient was followed up for a period of 2 months and, during his return, tissue recovery was observed, without symptoms or recurrence. Therefore, psychogenic factors, such as stress and anxiety, can have a negative influence on the exacerbation and appearance of oral lichen planus.